Pengaruh Penerapan Aplikasi Presensi Face Recognition dan Lingkungan Kerja terhadap Produktifitas Kerja di PT. Mitra Komunikasi Selurer TAP Pemalang (Telkomsel Autorized Partner) - Evi Nur Afidoh; Honorata Ratnawati (Universitas Veteran Bangun Nusantara, 2024)
The Face Recognition application is a web-based application that utilizes facial recognition capabilities and city connectivity networks and is integrated with the system. The purpose of this application is to record employee entry and exit times. It automatically records time and determines electronic performance calculations. Face Recognition is also in use it in one of the companies, one of which is PT. TAP Pemalang Cellular Communications Partner, In carrying out operational work, especially at PT. TAP Pemalang Cellular Communication Partner (Telkomsel Authorized Partner) has been carried out on an electronic or digital basis via mobile phone. This is done to improve employee discipline, efficiency and corporate governance. PT. TAP Pemalang Cellular Communications Partner (Telkomsel Authorized Partner) implements the Patty application, which is an Android-based presence application that can be easily used. The technology used is cameras and employee location. The Patty application can monitor employees online starting from attendance, leaving, permission, illness, leave. The method used in this research is a quantitative method. With the research results of the face recognition variable (X1) where the result is tcount 52.952 > ttable 2.012 and the significant value is 0.000 < 0.05, it can be said that face recognition has a significant effect on work productivity. The work environment variable (X2) where the t-count result is 51.00 > 2.012 and the significant value is 0.000 < 0.05 so it can be concluded that the work environment has a significant effect on work productivity